Effect of Content Schema, Vocabulary Knowledge, and Reading Comprehension on Translation Performance - Reza Kafipour; Naghmeh Jahansooz (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2017)
Schemata refer to all kinds of knowledge which are gained throughout the lifetime. Few studies tried to integrate schema theory and the next two crucial factors in translation and learning which are vocabulary knowledge and reading comprehension. Thus, the present research aimed at delineating the potential effect of these three factors on translation performance of Iranian undergraduate students majoring in translator training. To this end, 172 Iranian undergraduate students majoring in translator training were selected based on two-step cluster sampling. To collect data, the participants answered a set of 6 open-ended questions to measure the students’ content schema along with a vocabulary size test, reading comprehension test, and translation task. To analyze data, Pearson correlation coefficient as well as stepwise multiple regressions was conducted through Statistical Package for Social Sciences (SPSS) version 17. Data analysis indicated that the independent variables significantly correlated with translation performance. In addition, multiple regressions analysis specified reading comprehension as the main contributing variable and content schema as the second in students’ translation performance. It also showed that vocabulary knowledge could not be a predicting factor in translation performance of the learners; the reason may refer to the inseparable component of their translation task that is dictionary. The results highlighted the role of content schema in translation performance of the learners.